Appraisal of the Impact of e-Banking and Cashless Society in the Nigerian Economy - Umanhonlen O. Felix, Umanhonlen I. Rebecca, Omoruyi K. Igbinoba (HATASO, USA (Management and Economics Research Journal), 2015)
The article appraises the impact of e-banking and cashless society in the Nigerian economy. The study explores various aspects of e-banking and cashless economy using the banking sector of the Nigerian economy as a focal point. Specifically, the paper articulates empirical opinions that highlight the possible ways these policy measures have direct links to beneficiaries and the weighted outcomes when divergence is noticed and how to bring back the soundness, sustainable and rebranding policy that ensures economic growth. The paper holds that for a sustainable cashless society to emerge all hands must be on desk; banks should de emphasize all odds and ensure that efficiencies of e-banking mechanisms are of utmost priority. It, therefore, recommends that adequate plans be in place to sensitize the general public about the effects and lay down procedures to check possible drawbacks. It, however, concludes by imploring all avenues and reports that relevant agency, service providers, operators, and those who have direct access to information to advocate as timely as when necessary about the implicit needs and benefits behind the cashless economy.
Appraisal of the e-Banking and Cashless Society on Economy
Keywords: e-Banking; Cashless economy; Nigerian economy